Successful transradial intervention via a radial recurrent artery branch from the radioulnar alpha loop using a sheathless guiding catheter - Yoon, Shin-Eui (Yeungnam Univ J Med, 2018)
The radial artery is generally the preferred access route in coronary angiography and coronary intervention. However, small size, spasm, and anatomical variations concerning the radial artery are major limitations of transradial coronary intervention (TRI). We describe a successful case involving a patient with coronary artery disease who underwent TRI via a well-developed radial recurrent artery branch from the radioulnar alpha loop using a sheathless guiding catheter.